Effect of ultrasonic vibration on residual stress in plasma cladding of iron-based alloy - Lai, Youbin; Yue, Wenwen; Zhang, Yichuan (Frontiers in Materials, 2023)
To explore the effect of ultrasonic vibration power and frequency on the residual stress of single-channel iron-based alloy plasma cladding, the single-factor ultrasonic vibration plasma cladding test was designed, and ten groups of single-channel iron-based alloy cladding samples under different process parameters were studied. The drilling method was used to measure the residual stress of the substrate at the beginning, middle and tail positions of each sample cladding layer. The residual stress of the substrate was analyzed and the significant characteristics of the effect of ultrasonic vibration power and frequency on the residual stress at different positions were explored using variance analysis. The results show that the residual stress is significantly reduced after applying ultrasonic waves. When the ultrasonic frequency is constant and the ultrasonic power is 240W, the residual stress of the formed sample is the smallest. Compared with the unapplied ultrasonic assistance, the residual stress in the X direction is reduced by 62.56%, and the residual stress in the Y direction is reduced by 63.23%. When the ultrasonic power is constant and the ultrasonic frequency is 28kHz, the residual stress of the formed sample is the smallest. Compared with the unapplied ultrasonic assistance, the residual stress in the X direction is reduced by 17.23%, and the residual stress in the Y direction is reduced by 19.79%. The ultrasonic power significantly affects the middle part of the cladding layer, and the ultrasonic frequency significantly affects each point of the cladding layer.